Repair and Conservation of the Four Courts Dome - Pavia, Sara; Aly, Marwa (My University, 2018)
The Four Courts was built between 1786 and 1802. Fire events, the 1922 civil war, pollution and exposure have damaged the building’s fabric. A conservation project by the Office of Public Works focussed on the dome, an outstanding structure built with limestone, fire-clay brick and granite. This paper presents the results of the material’s investigation prior to the restoration. There were concerns that the new concrete dome, placed after the civil war, had altered the loading path of the original timber structure and was now transferring the weight of the roof onto the Portland stone and brick parapet. The similar compressive strengths of the original Portland stone in the dome (50 MPa) and the quarry stone (41-54MPa) suggest that there is little or no strength loss due to permanent loading in time therefore, the stone is probably not carrying any loads. The strength of the granite is lower than expected. This was mainly attributed to the use of granite boulders and the different shapes of the specimens (cubes vs cylinders). Except for 2 granite specimens which showed significant bucking before failure, all Portland stone and granite specimens failed in axial splitting and shear fracture indicating a brittle behaviour. The bricks display common features of the historic Dublin range suggesting that they were made locally. Despite the presence of pebbles, lime inclusions and black core, the strength of the bricks is outstanding, similar (often superior) to contemporary machine-pressed brick ware. Their failure evidenced significant plastic behaviour. Fracturing due to expansion of iron fixings embedded in the Portland stone was identified. Several Portland soffit stones were face bedded resulting in the opening of cracks along the bedding. Petrography evidenced repairs made with crushed Portland stone and white Portland cement largely in good condition however, the introduction of some polymer-based composites resulted in advanced deterioration.
CERI 2018 Civil Engineering Research Association of Ireland
PUBLISHED
Keywords: The Four Courts; Conservation; Dome